2014
DOI: 10.1140/epja/i2014-14072-3
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic quarkonium photoproduction in hadron-hadron interactions at LHC energies

Abstract: In this paper we study the inelastic quarkonium photoproduction in coherent pp/pP b/P bP b interactions. Considering the ultra relativistic hadrons as a source of photons, we estimate the total h1 + h2 → h ⊗ V + X (V = J/Ψ and Υ) cross sections and rapidity distributions at LHC energies. Our results demonstrate that the experimental analysis of this process can be used to understand the underlying mechanism governing heavy quarkonium production.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 70 publications
(53 reference statements)
3
19
3
Order By: Relevance
“…In contrast, for the double J/ production, the contribution associated to the description of the QCD dynamics at high energies contributes significantly, mainly in pp collisions. Predictions for the RHIC, LHC, FCC, and CEPC-SPPC energies are shown.In recent years a series of experimental results from RHIC [1,2], Tevatron [3] and LHC [4][5][6][7][8][9][10][11][12] demonstrated that the study of photon-induced interactions in hadronic colliders is feasible and that it can be used to, among other things, improve our knowledge on the nuclear gluon distribution [13][14][15][16][17][18][19], on details of QCD dynamics [20][21][22][23][24][25][26][27][28][29][30], on the mechanism of quarkonium production [29][30][31][32][33][34][35][36], on the Odderon [37,38] and on the photon flux of the proton [39,40]. These data have stimulated the development of the theoretical description of these processes as well as the proposal of new forward detectors to be installed in the LHC [41,42].…”
mentioning
confidence: 99%
“…In contrast, for the double J/ production, the contribution associated to the description of the QCD dynamics at high energies contributes significantly, mainly in pp collisions. Predictions for the RHIC, LHC, FCC, and CEPC-SPPC energies are shown.In recent years a series of experimental results from RHIC [1,2], Tevatron [3] and LHC [4][5][6][7][8][9][10][11][12] demonstrated that the study of photon-induced interactions in hadronic colliders is feasible and that it can be used to, among other things, improve our knowledge on the nuclear gluon distribution [13][14][15][16][17][18][19], on details of QCD dynamics [20][21][22][23][24][25][26][27][28][29][30], on the mechanism of quarkonium production [29][30][31][32][33][34][35][36], on the Odderon [37,38] and on the photon flux of the proton [39,40]. These data have stimulated the development of the theoretical description of these processes as well as the proposal of new forward detectors to be installed in the LHC [41,42].…”
mentioning
confidence: 99%
“…The minimum value of the transverse momentum of the quarkonium is chosen at p Q T min = 1 GeV. The range of z J/ψ is selected from zero to the area near one (z J/ψ < 1) and the predictions are not strongly dependent on the inferior limit of the integration z J/ψ min [70]. Numerical calculations are carried out by in-house monte carlo generator.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In recent years a series of experimental results at RHIC [18,19], Tevatron [20] and LHC [21][22][23][24][25][26][27][28][29] demonstrated that the study of photon-induced interactions in hadronic colliders is feasible and can be used to probe e.g. the nuclear gluon distribution [30][31][32][33][34][35][36][37][38][39][40][41], the dynamics of the strong interactions [42][43][44][45][46][47][48][49][50][51][52], the Odderon [59,60], the mechanism of quarkonium production [51][52][53][54][55][56][57][58] and the photon flux of the proton [61,62]. It has stimulated the improvement of the theoretical description of these processes as well as the proposal of new forward detectors to be installed in the LHC …”
Section: Introductionmentioning
confidence: 99%